2000
DOI: 10.1002/(sici)1097-0266(200003)21:3<295::aid-smj91>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Do firms learn to create value? The case of alliances

Abstract: We investigate whether firms learn to manage interfirm alliances as experience accumulates. We use contract‐specific experience measures in a data set of over 2000 joint ventures and licensing agreements, and value creation measures derived from the abnormal stock returns surrounding alliance announcements. Learning effects are identified from the effects of unobserved heterogeneity in alliance capabilities. We find evidence of large learning effects in managing joint ventures, but no such evidence for licensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
297
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,239 publications
(335 citation statements)
references
References 40 publications
4
297
1
4
Order By: Relevance
“…However, approximately half of all strategic alliances fail (Kale, Dyer, and Singh, 2002). Indeed, the large gap between potential economic value creation and realized economic value creation in strategic alliances suggests that there are formidable impediments to successful alliance outcomes (Anand and Khanna, 2000;Gottschlag and Zollo, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately half of all strategic alliances fail (Kale, Dyer, and Singh, 2002). Indeed, the large gap between potential economic value creation and realized economic value creation in strategic alliances suggests that there are formidable impediments to successful alliance outcomes (Anand and Khanna, 2000;Gottschlag and Zollo, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Effective actions will more likely be repeated in the future. As Anand and Khanna [18] pointed out that one of the most important factors of alliance success is previous experience with alliances. Kale et al [17] argue that alliance experience helps firms to develop a relational capability.…”
Section: Collaborative Capability -A Multifaceted Conceptmentioning
confidence: 99%
“…In addition, research has unfolded that successful inter-organizational performance starts within each involved organization. Captured by the concept of alliance capability, previous studies have identified that alliance management success increases by the presence of supportive infrastructural facilities for gathering, generating, institutionalizing, and dispersing alliance management knowledge (Draulans et al, 2003;Kale and Singh, 2009), and stressed the importance of experience in alliance learning (Anand and Khanna, 2000). Researchers argued that such knowledge and experience contribute to the development of interorganizational coordination mechanisms such as trust, and discovered that organizations with such a knowledge base are more successful in alliances than those without (Bamford et al, 2003).…”
Section: Scientific Perspectivementioning
confidence: 99%
“…Referred to as alliance capability, they explored organizational competencies (series of activities and processes) which can positively influence the alliance outcome (Sluyts et al, 2012). Their studies in particular focused on developing alliance capability by means of learning from past collaborative experience to overcome future challenges (Anand and Khanna, 2000). Since an organizational capability usually acts as a co-specialized element in the organizational system (Vesalainen and Hakala, 2014), alliance capability not only depends on organizational learning capability.…”
Section: Rq 5: Which Factors Are Likely To Affect Differences Betweenmentioning
confidence: 99%
See 1 more Smart Citation